(untitled) (International Journal of Studies in Nursing, 2024)
Background: Idiopathic scoliosis is commonly found in adolescents of 10 to 17 years of age, patients are required to encounter several essential measures and types in treatment. Healthcare team provides patients with complete and continuous treatment, in which a comprehensive care criterion has been a crucial issue. Aim: This article aims to develop a care criterion tool with reliability and validity. Subject and methods: By using cross-sectional study, a care criterion is developed with literature review. Moreover, the contents were reviewed by experts which further modified based on nursing personnel’s recommendation after actual use among clinical patients. Results: The “Care Journey Map for Scoliosis Patients” with contents of 72 items had been completed, in which the expert validity was 0.98. After use by nursing personnel, items with 100% completeness achieved 76.2%, the overall satisfaction from nursing personnel was 89.9% and 100% agreed the completeness and significance of this care map. Conclusion: The “Care Journey Map for Scoliosis Patients” is a care criterion developed based on literature review by nursing experts with years of clinical experience, considering transverse and longitudinal time axes as main parts for the overall process in patient care. The tool is proved to be with reliability and validity, which can be a care criterion provided for clinical nurses’ compliance, meriting clinical promotion.